Does Concentration Matter for Bank Stability? Evidence from the Albanian Banking Sector - Gerti Shijaku (Journal of Central Banking Theory and Practice, 2017)
Motivated by the debate on the concentration-stability nexus, this paper studies the impact of bank concentration on the likelihood of a country suffering systemic bank fragility. For this reason, we followed a new approach using on-site bank balance sheet information to construct our proxy that represents each bank stability condition and uses a variety of internal and external factors to estimate a balance panel dynamic two-step General Method of Moments (GMM) approach for the period 2008 – 2015. First, results provide supportive evidence consistent with the concentration-fragility view. Second, macroeconomic variables seem to have a significant effect on bank stability, which is not found for the sovereignty primary risk. By contrast, the bank-specific variables have also a significant effect on bank stability conditions. Finally, non-systemic banks are found to be more sensitive to macroeconomic condition and market concentration, while the better capitalised banks are less sensitive to fragility at the expense of lower operation efficiency.
Keywords: C26; E32; E43; G21; H63; 330; Bank Fragility; Primary Sovereignty Risk; Panel Data; Dynamic GMM